Efficacy of transcranial magnetic stimulation in anorexia nervosa: a systematic review and meta-analysis - Amir Reza Bahadori; Parisa Javadnia; Sanaz Bordbar; Rasa Zafari; Tina Taherkhani; Afshan Davari; Abbas Tafakhori; Sajad Shafiee; Sara Ranji (Eating and Weight Disorders)
Abstract Purpose Transcranial magnetic stimulation (TMS) has emerged as a promising treatment for various neuropsychiatric conditions, including depression, obsessive–compulsive disorder, and Parkinson's disease. Recent research has focused on evaluating its effectiveness in treating patients with anorexia nervosa (AN). This systematic review and meta-analysis examined the impact of TMS on patients with AN and evaluated any potential adverse effects. Methods We conducted search according to PRISMA guidelines and comprehensively analyzed data from multiple databases, including Pubmed, Scopus, Embase, Web of Science, and the Cochrane Library, up to September 13th. Statistical analysis utilized the Comprehensive Meta-analysis software version 3.0. Results The systematic review encompassed 17 studies, with nine undergoing meta-analyses. The primary target for TMS was the dorsolateral prefrontal cortex, with two studies targeting the dorsomedial prefrontal cortex, one targeting the insula and one targeting the inferior parietal lobe. The findings revealed a significant increase in body mass index (BMI) following TMS (SMD: −0.025, 95% CI: −0.0505 to −0.005, P-value = 0.045). Additionally, the Eating Disorder Examination Questionnaire (EDE-Q) score was quantitatively reported in six studies, which permitted its inclusion in the meta-analysis. The analysis exhibited a significant decrease in EDE-Q score after TMS (SMD: 0.634, 95% CI: 0.349–0.919, P-value < 0.001). Subgroup analysis based on TMS session duration indicated that the effect size of TMS on EDE-Q score is more pronounced when the session duration exceeds 20 min. Conclusion TMS represents an effective therapy for patients with AN, leading to improvements in both BMI and core symptoms of AN, with minor and transient side effects. Level of evidence Level I, systematic reviews and meta-analyses.